1997
DOI: 10.1046/j.1365-2958.1997.4881840.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inositol monophosphatase in Saccharomyces cerevisiae

Abstract: SummaryInositol monophosphatase is a key enzyme in the de novo biosynthesis of inositol and in the phosphoinositide second-messenger signalling pathway. Inhibition of this enzyme is a proposed mechanism for lithium's pharmacological action in bipolar illness (manic depression). Very little is known about how expression of this enzyme is regulated. Because the yeast Saccharomyces cerevisiae has been shown to be an excellent model system in which to understand the regulation of inositol metabolism, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Both drugs, in therapeutically relevant concentrations, cause a decrease in intracellular inositol mass and an increase in expression of a structural (INO1) and a regulatory (INO2) gene required for inositol synthesis. The mechanism of inositol depletion by lithium is most likely by inhibition of inositol monophosphatase, as previous studies have shown that lithium inhibits yeast inositol monophosphatase activity and reduces expression of the INM1 gene (17,31). We propose that the mechanism of inositol depletion by valproate is most likely via inhibition of Ins-1-P synthase.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Both drugs, in therapeutically relevant concentrations, cause a decrease in intracellular inositol mass and an increase in expression of a structural (INO1) and a regulatory (INO2) gene required for inositol synthesis. The mechanism of inositol depletion by lithium is most likely by inhibition of inositol monophosphatase, as previous studies have shown that lithium inhibits yeast inositol monophosphatase activity and reduces expression of the INM1 gene (17,31). We propose that the mechanism of inositol depletion by valproate is most likely via inhibition of Ins-1-P synthase.…”
Section: Discussionmentioning
confidence: 52%
“…A likely mechanism for the lithium-induced decrease is via inhibition of inositol monophosphatase activity (17,31,34). We propose that valproate leads to decreased inositol by inhibition of the Ins-1-P synthase reaction.…”
mentioning
confidence: 89%
“…It is apparent that lithium exerts an effect on intracellular second-messenger systems in which activated receptorligand complexes stimulate the turnover of inositolcontaining phospholipids (del Rio et al 1998;Feldman et al 1997;Murray and Greenberg 1997;Soares et al 1999). Lithium's inhibitory action on receptor-mediated signal-transduction pathways has been demonstrated in vitro (Atack et al 1995) showing that it reduces myoinositol levels by non-competitively inhibiting the enzyme inositol monophosphate, a catalyst for converting inositol monophosphate hydroxyls to myo-inositol (Manji et al 1996).…”
mentioning
confidence: 99%
“…Lithium's inhibitory action on receptor-mediated signal-transduction pathways has been demonstrated in vitro (Atack et al 1995) showing that it reduces myoinositol levels by non-competitively inhibiting the enzyme inositol monophosphate, a catalyst for converting inositol monophosphate hydroxyls to myo-inositol (Manji et al 1996). Since the phosphoinositide cycle (PI) regulates a wide variety of neuronal functions, including intracellular calcium mobilization and protein kinase C (PKC) activity (Feldman et al 1997), lithiuminduced modification of the PI cycle has been proposed as a potential therapeutic mechanism underlying its mood-stabilizing effect (Berridge et al 1982;del Rio et al 1998;Murray and Greenberg 1997;Soares et al 1999). Although brain tissue can synthesize myo-inositol de novo , the ability of neurons to maintain a steady-state supply of cytosolic myo-inositol appears to be crucial to the resynthesis of phosphoinositides, and, conceivably, to the membrane receptor response to stimulation and neuronal homeostasis.…”
mentioning
confidence: 99%
“…To prepare overnight cultures, yeast cells were inoculated from colonies on YPD plates (yeast extract (1% w/v), bacto-peptone (2% w/v), glucose (2% w/v), agar (2% w/v)) into minimal synthetic medium (glucose (2% w/v), the essential amino acids and nucleotides (histidine (10 mg l −1 ), leucine (60 mg l −1 ), methionine (10 mg l −1 ), tryptophan (10 mg l −1 ) and uracil (10 mg l −1 )), vitamin free yeast base (0.069% w/v), ammonium sulfate (0.201%), vitamins 29 and myo-inositol (75 M)) and grown overnight at 30°C with aeration. Cells were harvested by centrifugation (10°C, 5000 rpm, 5 min), washed twice with 50 ml inositol-free minimal medium, and resuspended in 25 ml of this medium.…”
Section: Effect Of Inositol Isomers On Growth Of Inositol Auxotrophmentioning
confidence: 99%